Enhancing the coercivity, thermal stability and exchange coupling of nano-composite (Nd,Dy,Y)–Fe–B alloys with reduced Dy content by Zr addition - Zhao, L. Z. (2014)
With the intention to reduce Dy content in NdFeB based magnets, 50 at.% Y substituting Dy was previously successfully employed to improve the remanence and thermal stability of the nanocomposite [Nd0.8Dy0.2]10Fe84B6 alloy without the energy product reduction. In this work, introducing Zr into Y substituted alloys has enhanced the coercivity Hcj of the melt spun [Nd0.8(Dy0.5Y0.5)0.2]10Fe84−xB6Zrx alloys. With increasing x value from 0 to 2, Hcj increased from 575 to 814 kA/m. Doping 2 at.% Zr reduced the absolute value of the temperature coefficient β from 0.394 to 0.348%/°C. Good magnetic properties with Hcj of 797 kA/m, maximum energy product (BH)max of 131 kJ/m3 and β of −0.356%/°C were obtained for x = 1.5. Both the Curie temperature and lattice constants of the hard magnetic phase decreased with Zr addition, indicating that Zr atoms can substitute directly into the hard phase, although some atoms may also locate outside the lattice. Together with the analysis on the demagnetization curve and recoil loops, the results verified that a small amount of Zr can improve the coercivity, thermal stability and exchange coupling of nanocomposite NdDyYFeB alloys through enhancing the anisotropy and improving the microstructure.